Standards für die ökonomische Bildung in der gestuften Lehrerausbildung - Gerd-Jan Krol; Dirk Loerwald; Andreas Zoerner (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2006)
The German education system is currently undergoing a reorientation from formerly exclusively input-based control towards output-based measures of quality assurance in schools and universities. A crucial instrument in this reform process is the implementation of educational standards. This article focuses on the question of how standards in teacher-training for economic education can be conceptualised for a bachelor/master framework. For this purpose, it is necessary to outline the theoretical foundation of standards for economic education, since the latter is usually nationwide institutionally embedded in integrated subjects such as Social Sciences. From our point of view, economics has to serve as the central domain-specific reference point for the development of standards in economic education. On the basis of this framework we developed a recommendation of core competencies and of minimum standards derived from the former. Conclusively, the theoretical issues are illustrated by the model of teacher-training in economic education at Münster University.
Keywords: 330; Lehrkräfte; Berufsausbildung; Wirtschaftspädagogik; Deutschland